Exploring the learnability and usability of a near field communication-based application for semantic enrichment in children with language disorders. - Lorusso, Maria Luisa; Biffi, Emilia; Molteni, Massimo; Reni, Gianluigi (Assistive Technology, 2018)
Recently, a few software applications (apps) have been developed to enhance vocabulary and con- ceptual networks to address the needs of children with language impairments (LI), but there is no evidence about their impact and their usability in therapy contexts. Here, we try to fill this gap presenting a system aimed at improving the semantic competence and the structural knowledge of children with LI. The goal of the study is to evaluate learnability, usability, user satisfaction and quality of the interaction between the system and the children. The system consists of a tablet, hosting an app with educational and training purposes, equipped with a Near Field Communication (NFC) reader, used to interact with the user by means of objects. Fourteen preschool children with LI played with the device during one 45-minute speech therapy session. Reactions and feedbacks were recorded and rated. The system proved to be easy to understand and learn, as well as engaging and rewarding. The success of the device probably rests on the integration of smart technology and real, tangible objects. The device can be seen as a valuable aid to support and enhance communication abilities in children with LI as well as typically developing individuals.